Morphometric relationships for Copaifera langsdorffii (Desf.) Kuntze in northern region of Minas Gerais state, Brazil - Silva, Caio Ferreira da; Gama, Drauzio Correia; Araújo, Lais Almeida; Bahia, Jean Barcello Xavier; Lima, Vinícius Orlandi Barbosa (Revista Ecologia e Nutrição Florestal - ENFLO, 2020)
Copaifera langsdorffii specie occurs throughout Brazil and is of great economic importance, mainly due to its production of oil-resin used for various pharmacological purposes. The objective of this study was to analyze the morphometric relationships in C. langsdorffii stand in northern region of Minas Gerais state, Brazil. Twenty trees were randomly sampled and were measured: stem circumference at 1.3 m height, total height (Ht) and crown diameter (CD). Morphometric indices were estimated. Correlations between dendrometric and morphometric variables were obtained through the Pearson matrix. The morphometric relations of crown proportion (CP), crown area (CA), formal of crown (FC), degree of slenderness (DS), salience index (SI), coverage index (CI) and vital space (VS) presented values of 15.26%, 25.06 m², 1.47, 16.35, 21.70, 0.47 and 7.01, respectively. Strong positive correlations were found in: diameter at breast height (DBH) in relation to CD and CA; Ht with crown proportion (CP) and DS; the formal of crown (FC) with the CI and VS, and between the CI and VS. The morphometric indices made it possible to understand the few magnitude of stand variation. The species can be characterized as facilitating management.